Tracing the Itinerant Path : Jishū Nuns of Medieval Japan - Griffiths, Caitilin J. (Book collections on Project MUSE., 2017)
This study introduces the jishū nuns who participated alongside monks as fellow practitioners - not as wives, daughters, or mothers. They were partners in a Pure Land religious school devoted to encompassing the world with the name Amida Buddha through their continuous chanting of the nembutsu.